KAJIAN JENIS DAN KELIMPAHAN REKRUTMEN KARANG DI PESISIR DESA KALIBUKBUK, SINGARAJA, BALI - I Nyoman Dodik Prasetia (Bumi Lestari Journal of Environment, 2013)
AbstractKalibubuk coastal area is one nautical tourism destination in Buleleng regency. Higherlevels used zone in coastal area especially coral reef ecosystem is not balanced with thestudy of the potential and carrying capacity of the environment, especially coral reefs.Coral settlement times to substrate is a critical phase that will determine the success ofcoral sexual reproduction. Success in forming coral reefs will determine the sustainabilityof coral reef ecosystems. The study was conducted in March and October 2011, aims todetermine the pattern of spread of juvenile corals, species, abundance and survival ofjuvenile coral patterns and the physical, chemical, and biological factor. The study wasconducted at a depth of 5 meters with 3 shelves on each research station research. A rackconsists of 24 pieces of substrate with 4 different positions against the current. Juvenilecorals were found to be composed of nine species of coral and 109 individuals. Juvenilecorals are found at all stations in the study with the largest number of Station 3 as many as59 individuals. Physical, chemical, and biological factor in Kalibukbuk relatively stillsupport the growth and development of juvenile coral into coral colonies.